Developing Students’ Writing Skill By Using Webquest - Anggita Anggita; Edy Sutrisno; Novi Desanti (Eksos, 2019)
Many Polytechnic’s students are not interested in writing and lose their enthusiastic. They often have many basic mistakes in written works and get low scores when doing writing tests. It is very difficult for them to come up with ideas and organize these ideas using an appropriate choice of vocabulary, sentence and paragraph organization, and translate these ideas into a readable text. Based on that problem, therefore, the main objective of this research is to examine to what extent the use of webquest can develop the writing skill of POLNEP’s students and to identify the mistakes of students’ writing skill in terms of content, grammar, organization, vocabulary, and mechanics. This research was a Classroom Action Research (CAR) which was carried out at Business Administration Department of Pontianak State Polytechnic. The population of this research was the fourth semester students of Business Administration Department of Pontianak State Polytechnic in the academic year of 2017/2018. The sample of this study was chosen because the students in this class had the lowest average score of writing test among the other classes. The total number of the students was 29. The procedure of the cycle consists of planning, acting, observing, and reflecting. This research used a number of data collection tools including writing test, semi-structured interview and observation. To analyze the data, the researcher used students’ writing test results which was scored by consulting the writing scoring rubric. To avoid subjectivity and personal bias of writing score, the researcher used inter-rater. The findings of the study showed that the use of Webquest develops students’ writing skill. Their writing improved syntactically and grammatically from draft to draft in the cycle. The students can manage to write longer paragraph with clear topic sentence and some related supporting ideas. They produce less mistakes in word order, tenses, sentence pattern, and other grammar forms. Besides, they show that they use wide vocabulary and sentence variety in their writing. The result proves positive insight that webquest is one of appropriate method to develop students’ writing skill.